LANGUAGE POLICY IMPLEMENTATION IN LATVIAN PRE-SCHOOL: LATVIAN LANGUAGE SKILLS OF MINORITY CHILDREN - Markus, Dace; Zīriņa, Tija; Markus, Kārlis (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
Latvian is the only official language in Latvia and one of the symbols of an independent state. The article provides a brief insight into the history of its reinforcement, which has not been easy. Education is one of the areas in which it is very important to develop multilingualism, while not forgetting to strengthen state language skills and their application. As the education system continues to reveal shortcomings in the process of Latvian language acquisition, Cabinet Regulations adopted in 2018 “Regulations Regarding the State Guidelines for Pre-school Education and the Model Pre-school Education Programmes” update the need for a successful transition from pre-school education to primary education at school, from pre-school education to bilingual primary school education or education carried out in Latvian. In minority families with a dominant Russian language, children acquire Russian well before pre-school age, and it is time to start learning the state language at pre-school age if this has not already been done. Taking these requirements into account, the article analyses the Latvian language skills of children of pre-school age, using 375 child speech recordings made by researchers in 2019 and 2020 in three regions – Kurzeme (Western Latvia), Latgale (Eastern Latvia), and Riga (capital). The materials are divided into three groups in each of the territories: recordings of Latvian children, recordings of minority children in groups with the Latvian language on a daily basis, and recordings of minority children in groups with the Russian language on a daily basis. The main problem is that regardless of the region, the Latvian language skills of minority children who attend pre-school education groups with a dominant Russian language on a daily basis are still insufficient and do not comply with the requirements set in Cabinet Regulation No. 716 of 2018 that the children should be prepared to start school with the Latvian as the learning language or bilingually. This suggests that the legislative provisions are not fully implemented and improvements are necessary for the Latvian language training system for minority children.